1985
DOI: 10.1227/00006123-198510000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgery for Giant Craniopharyngiomas in Children

Abstract: The authors report 20 cases of giant craniopharyngioma in children operated on during the 6-year period from 1978 through 1984. The tumor size (maximal diameter) ranged from 5 to 11 cm. These patients presented with increased intracranial pressure, severe visual loss, and neurological and endocrinological deficits. Tumor growth had occurred in several directions, causing displacement of the circle of Willis, the optic apparatus, and the hypothalamus, as well as encroachment into the interpeduncular and prepont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 0 publications
1
31
0
Order By: Relevance
“…1,3,8,9,37 Not only is the size of the tumor gaining attention, but also its extension into multiple compartments (subarachnoid spaces). Thus, we advocate using the term "extensive craniopharyngioma" for a craniopharyngioma that extends into many compartments other than the chiasmatic cistern and attains a size larger than 4 cm.…”
Section: ©Aans 2014mentioning
confidence: 99%
See 1 more Smart Citation
“…1,3,8,9,37 Not only is the size of the tumor gaining attention, but also its extension into multiple compartments (subarachnoid spaces). Thus, we advocate using the term "extensive craniopharyngioma" for a craniopharyngioma that extends into many compartments other than the chiasmatic cistern and attains a size larger than 4 cm.…”
Section: ©Aans 2014mentioning
confidence: 99%
“…37 Al-Mefty et al reported a 90% rate of giant craniopharyngioma resection in those operations he personally performed using a sophisticated petrosal approach, and a 30% resection rate in a series of patients previously operated on by other surgeons. 3 Gardner et al reported complete resection in 8 of 11 patients in whom total resection was planned, in a total series of 16 patients with variable tumor sizes and extensions. 11 …”
Section: Extent Of Tumor Resectionmentioning
confidence: 99%
“…They are the most common non-glial tumors in childhood 2 and originate from the embryonic remains of squamous cells through the hypophyseal-pharyngeal duct.…”
Section: Introductionmentioning
confidence: 99%
“…There are frequent fluctuations in sodium level in the postoperative period such that patients at times exhibit diabetes insipidus and at other times inappropriate secretion of antidiuretic hormone, progressing with either hypernatremia or hyponatremia that is difficult to control and may lead to severe brain damage or even death. Patients may also exhibit hyperphagia, obesity, low stature and psychiatric disorders in the later postoperative period 1,2,4 . There is no consensus in the literature on the best way to treat an adamantinomatous craniopharyngioma in childhood.…”
Section: Introductionmentioning
confidence: 99%
“…19 Other authors report increased mortality, 94 increased neurological and hypothalamic morbidity, 14,22,94 decreased extent of resection and local disease control, 14,16,23,27,28,39,46,68,74,86,91 and higher rates of tumor recurrence 14,22,29,34,83,91 in larger tumors. Some authors, however, report tumor size or volume to have no impact on extent of resection, 2,4,50,88,95 rate of recurrence 49,63 or hypothalamic morbidity. 63 Various treatment strategies have been proposed to combat these difficult tumors, including cyst aspiration, 30,78 intracavitary irradiation 33,61,89 or chemotherapy, 32,37,82 radical resection, 2,95 or limited resection plus RT for tumors of all sizes.…”
mentioning
confidence: 99%